Cytotoxic Effects of Luteolin Isolated from Feronia limonia Linn. - Hanchinalmath, Jayashree; Londonkar, Ramesh; Shivasharanappa, Kirankumar (Asian Journal of Biological and Life Sciences, 2020)
Aim:To evaluate cytotoxic properties ofFeronia limoniaLinn. in different test systems.Methods:In the present study, we have evaluated germination of green grams, viability of yeasts and potato disc assay for rapid and inexpensive screening of drugs exhibiting cytotoxic properties of the isolated compound in comparison with the standard drug. Seed germination parameters- rootlet growth and inhibition were assayed. Yeast viability by spectrophotometric and methylene blue staining method.Results:Zone of inhibition study againstAgrobacterium tumefaciensand potato disc assay has shown a distinct interference of plant extracts against tumor formation and bacterial growth, there by its effect is attributing to antitumor and growth inhibitor properties.Conclusion:This screening test helps in identifying the potential plant types that can be used for medicinal purposes against specific microbe and also as a nutritional supplement for fighting against the free oxide radicals.
Keywords: Agrobacterium tumefaciens; Herbal extracts; Potato disc; Seed germination; Yeast